Reformulation of Rehabilitation Arrangements for Narcotics Addicts and Victims of Narcotics Abuse: Reformulasi Pengaturan Rehabilitasi Terhadap Pecandu Narkotika dan Korban Penyalahgunaan Narkotika - Mukhoyyaroh, Vina Durrotul (Annual Review of Legal Studies, 2024)
The large number of criminal cases of narcotics abuse that are sentenced to imprisonment in the jurisdiction of Semarang City, has resulted in violations of the rights of narcotics addicts and victims of narcotics abuse. Even though it has been clearly explained in Law Number 35 of 2009 concerning Narcotics, which requires the punishment for narcotics addicts and victims of narcotics abuse, namely rehabilitation. This research aims to determine the implementation of rehabilitation for narcotics addicts and victims of narcotics abuse in Semarang City and to reformulate rehabilitation arrangements. This research uses a qualitative approach with an empirical juridical type of research. Data sources come from primary data and secondary data and data validity is carried out using the Triangulation method and described using an interactive model. The results of the research show that the implementation of rehabilitation for narcotics addicts and victims of narcotics abuse in Semarang City has not run optimally, which is due to inconsistencies in rehabilitation arrangements in Indonesia and several weaknesses in the arrangements for implementing integrated assessments. Therefore, it is necessary to reformulate rehabilitation arrangements in Law Number 35 of 2009 concerning Narcotics, which contains regulations for implementing a comprehensive integrated assessment process that prioritizes expediency and justice in handling criminal cases of narcotics abuse. Apart from that, there needs to be a common understanding of rehabilitation provisions by law enforcement officials, with the aim that the implementation of rehabilitation for narcotics addicts and victims of narcotics abuse can run effectively and optimally. There are important points in reforming rehabilitation arrangements, such as the redefinition of the terms narcotics addict and narcotics abuse victim, the evidentiary strength of assessment results by the Integrated Assessment Team (TAT), and the application of the Rechterlijk Pardon concept for narcotics addicts and narcotics abuse victims.